Effects of vibroacoustic stimulation in music therapy for palliative care patients: a feasibility study - Warth, Marco; Keßler, Jens; Kotz, Svenja; Hillecke, Thomas; Bardenheuer, Hubert J. (BMC complementary and alternative medicine, 2015)
The present study aimed at examining whether methodological strategies from a previously implemented study design could be transferred to the evaluation of the psychological and physiological effects of a music therapy intervention working with vibroacoustic stimulation in palliative care.